Analysis of the knowledge of hepatitis C virus among the patients - Marta Estera Kowalska; Paweł Kalinowski; Urszula Bojakowska (Kazimierz Wielki University, 2018)
Background Hepatitis C is currently one of the most serious epidemiological problems worldwide. Due to no specific method of prevention, prophylactic measures focus on spreading the knowledge about the routes of infection with the virus and risk factors for contracting the disease as well as the situations which increase the probability of virus transmission. Objective To evaluate of the knowledge of the patients about hepatitis C. Material and Methods The study was conducted in 2014 with the use of an original questionnaire among 200 patients of the Department of Infectious Diseases at the Medical University of Lublin and the members of support groups for HCV patients in Lublin and Warsaw. The questionnaire included some questions about the risk factors for HCV infection, the course and symptoms of hepatitis C and the sources of information about the disease. Results Most of the respondents associate the risk of HCV infection with the provision of health services whereas they know much less about other routes of transmission. More than 25% of the subjects describe their level of knowledge about the disease as insufficient. Conclusions The level of knowledge of the study group is good but it needs to be upgraded as it was pointed out by the respondents themselves. The main sources of knowledge about hepatitis C are doctors and the Internet. Few respondents obtained their knowledge from other media, which may mean that the problem of HCV infection received little publicity, which in turn translates into poor awareness of the general population.